Moving Beyond Screen Time Redefining Developmentally Appropriate Technology Use in Early Childhood Education - Daugherty, Lindsay (RAND Corporation, 2014)
Using screen time as the primary measure of "developmentally appropriate" technology use by young children has become increasingly inappropriate as new technologies are introduced and as we learn more about the potential benefits of technology. The authors challenge the traditional emphasis on screen time and discuss how to move toward a more comprehensive definition of developmentally appropriate technology use in early childhood education.